ANALISIS SALURAN PEMASARAN INDUSTRI TAHU DIKECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI - Henny Pratiwi; Insan Fahmi (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Under the guidance of Mr. Dedi Kusbiantoro, S.P., M.M. as chairman of the supervisory commission and Mrs. Hj. Henny Pratiwi, S.P., M.M. as a member of the advisory committee. The purpose of this study was to determine the pattern of tofu marketing channels, to analyze tofu marketing costs, profits and margins; and to analyze the level of economic efficiency of each tofu marketing channel in Dolok Masihul District, Serdang Bedagai Regency. The choice of research location was done purposively. The sample in this study were 19 respondents who owned the tofu industry. Field research was conducted from March 2022 to April 2022. The method used is marketing margin analysis to determine differences in price levels in marketing channels, this study also uses farmer's share analysis to determine marketing efficiency. The results of the study concluded that the fried tofu housing industry in Dolok Masihul District has 2 (two). In marketing channel I, the total marketing cost is Rp. 30/ptg, the total marketing profit for retailers is Rp. 303.33/ptg, and the marketing margin is Rp. 83.33/ptg. For marketing channel II there is no marketing fee. On stock farmers that marketing channels I and II are included in the efficient category.